The not so hidden impact of interictal burden in migraine: A narrative review - Vincent, Maurice; Viktrup, Lars; Nicholson, Robert A.; Ossipov, Michael H.; Vargas, Bert B. (Frontiers in Neurology, 2022)
Migraine is a highly prevalent neurological disease of varying attack frequency. Headache attacks that are accompanied by a combination of impact on daily activities, photophobia and/or nausea are most commonly migraine. The headache phase of a migraine attack has attracted more research, assessment tools and treatment goals than any other feature, characteristic, or phase of migraine. However, the migraine attack may encompass up to 4 phases: the prodrome, aura, headache phase and postdrome. There is growing recognition that the burden of migraine, including symptoms associated with the headache phase of the attack, may persist between migraine attacks, sometimes referred to as the “interictal phase”. These include allodynia, hypersensitivity, photophobia, phonophobia, osmophobia, visual/vestibular disturbances and motion sickness. Subtle interictal clinical manifestations and a patient’s trepidation to make plans or commitments due to the unpredictability of migraine attacks may contribute to poorer quality of life. However, there are only a few tools available to assess the interictal burden. Herein, we examine the recent advances in the recognition, description, and assessment of the interictal burden of migraine. We also highlight the value in patients feeling comfortable discussing the symptoms and overall burden of migraine when discussing migraine treatment needs with their provider.